Bioprospecting of bacillus pumilus ngp-2 for the production Of proteinaceous α-amylase inhibitor - SURAYYA IK MOHAMMED; SHANMUGARAJU VEERAMUTHU; ANJALI ARAVIND; BIVYA P.G (International Journal of Pharma and Bio Sciences, 2017)
The study was conducted to screen the proteinaceous α-amylase inhibitory activity of Bacillus pumilus NGP-2. The culture free supernatant was precipitated by ammonium sulfate at 10-80% saturation for overnight at 4ºC. The precipitated proteins were desalted by dialysis and the protein content was estimated as 0.5mg/ml. The proteinaceous α-amylase inhibitor was subjected to Preparative High Performance Liquid Chromatography. Two fractions were collected and α-amylase inhibitory activity was checked. Fraction I showed α- amylase inhibitory activity of 64%.The molecular weight of the α-amylase inhibitor was determined by Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis as 65 kDa. The results suggested that the proteinaceous α-amylase inhibitor from Bacillus pumilus NGP-2 may be a potent inhibitor and can find role in the management of post prandial hyperglycemia.